'A one-sided view of the world': women of colour at the intersections of academic freedom. Issue 10 (26th November 2022) - Blell, Mwenza; Liu, Shan-Jan Sarah; Verma, Audrey
ABSTRACT: Academic freedom is a necessary principle. Current attempts to (re)conceptualise, (re)frame, and reduce the principles of free speech from universal concepts to specific and narrow conceptions are however underpinned by political expediency and accompanied by erosions to press freedom and protest rights. The current enacting and policing of academic freedom is purposely acontextual, colour-blind, and ignorant of differential costs of dissent and (non)compliance. This paper focuses instead on the interlinked conditions of precarity, neoliberalisation, internationalisation, digitisation, and state-encouraged intervention that lead to increased surveillance, (self-)censorship, and cultures of silencing, to show that women and people of colour are caught in the crosshairs of the 'culture wars' in unique ways. Drawing primarily on the United Kingdom Higher Education (UKHE) sector alongside other international examples, this paper contends that the conditions, structures, and policies around research and teaching amplify state-encouraged backlash against the teaching and research on specific topics. It shows that the renewed fervour for academic freedom continues to disguise bad faith ideologies whilst amplifying politicised interests keen to reinforce the status quo. Historically excluded and minoritised academics face new risks and greater pressures building on already deep-rooted institutional cultures of targeted silencing.